2015
DOI: 10.12968/jowc.2015.24.10.452
|View full text |Cite
|
Sign up to set email alerts
|

Hand amputations: epidemiology, management and resurfacing options for soft tissue coverage

Abstract: Agricultural hand injuries are not totally avoidable and their incidence can be reduced by proper education, but the low economic and literacy status of the patients is a big hurdle. The forearm offers many flaps for reconstruction of hand, which can be used in defects on dorsal or palmar aspect of hand and results in early discharge from the hospital and early rehabilitation. In patients with associated injury to the forearm, abdominal flaps can be used for cover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This is in accordance with the other study shown an association of lower socioeconomic status with higher hand amputation (Khurram et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
“…This is in accordance with the other study shown an association of lower socioeconomic status with higher hand amputation (Khurram et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
“…Several other machines are involved in upper extremities injuries such as grain augers, hay balers, power take-off, wheat threshers, and corn pickers. Often these injuries caused by these machines are mutilating and represent a real emergency, requiring major surgery [30,[63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies report that irrigation and surgical debridement are needed for most of the cases [28][29][30]. In Grandizio's study 2018 [28], patients with upper extremities injuries are more likely to require surgery and to be readmitted to hospital than those with other kind of lesions, especially with some risk factors for readmission such as age > 18 years, falls from height and surgery.…”
Section: Cross Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft tissue defects on the hand require good flap cover for proper rehabilitation. There are a few types of flaps from the same forearm which could be used to cover the hand defects with the major advantage of a shorter hospital stay [6].…”
Section: Discussionmentioning
confidence: 99%